2021
DOI: 10.30684/etj.v39i9.1775
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wavy Fins on Thermal Performance of Double Pass Solar Air Heater

Abstract:  New arrangements of the wavy fins structure were implemented on the absorber.  The wavy fins obstruct the flow on both passes of the double passes collector.  Thermal efficiency reached 84% with the new arrangements.In this paper, experimental study on double pass solar air heater with wavy fins absorber has been investigated. The fins attached to the upper and lower surfaces of the absorber. Two wavy fins arrangement (3 and 7 fins) have been investigated with plan absorber by changing solar radiation inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…However, the current study focuses on applying heat exchangers with serpentine, wavy fins in solar water heaters. The latest discoveries validate the effect of the heat source on the system's thermal efficiency [21].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the current study focuses on applying heat exchangers with serpentine, wavy fins in solar water heaters. The latest discoveries validate the effect of the heat source on the system's thermal efficiency [21].…”
Section: Introductionmentioning
confidence: 96%
“…Thus, the water temperature rises rapidly because it has little mass. An air heater driven by sunlight and wavy fins linked to the absorber in parallel with the airflow was employed in an experimental study [21]; the greater number of waves in the fin indicated higher efficiency. Along with comparing the absorption and performance of the fins, the impacts of fin arrangement, flow, and solar radiation intensity on thermal efficiency were also examined.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Das et al [16] enhanced the convective heat transfer coefficient by up to 17% by creating artificial roughness by mixing the sand particles with the black paint. Jalil et al [17] tested the effect of installing wavy fins of 3 and 7 waves on the solar flat plate absorber, and they succeeded in improving the thermal performance by about 84% as compared with the conventional collector. Sudhakar and Cheralathan [18] improved the thermal performance by up to 17.4% by replacing the conventional flat plate absorber with V-groove absorber with pin fins on its two sides.…”
Section: Introductionmentioning
confidence: 99%
“…Investing in the solar energy field contributes to minimizing CO2 levels and global warming since the systems that are used for converting solar irradiance into other's energy forms produce no pollutants (Khanmohammadi et al 2021). Solar energy can be converted directly into electricity via photovoltaic panels (Monna et al 2022) or into heat via many systems such as solar air heaters (SAHs) (Jalil et al 2021), solar water collectors (Shafiee et al 2022), solar chimneys (Karimipour-Fard and Beheshti 2017), etc. Solar air heaters are utilized in many applications such as supplying hot air in agriculture dryers for drying agricultural crops and fruits as well as supplying hot air in buildings especially in the winter season to make it comfortable for living (Razak et al 2016).…”
Section: Introductionmentioning
confidence: 99%